A Novel Method to Control the Crystallographic‐Preferred Orientation of Lead Iodide Toward Highly Efficient and Large‐Area Perovskite Solar Cells. Issue 10 (10th October 2022) - Chiu, Pei-Ting; Tung, Yung-Liang; Wu, Shih-Hsiung; Hsu, Hung-Chieh; Huang, Kuo-Wei; Kuo, Ming-Tsun; Yang, Sheng-Hsiung
Abstract : Perovskite Films In article number 2200609, Pei‐Ting Chiu and co‐workers found that the proportion of the facet (001) of PbI2 crystals increases as the synthesis temperature increases and fabricates better formamidinium‐based perovskite films. The perovskite solar cells based on the PbI2 synthesized at 120 °C exhibit the best power conversion efficiency (PCE) of 17.96% and the module with an active area of 3.68 cm 2 shows a PCE of 16.08%.